Homeopathic Treatment of Arabidopsis thaliana Plants Infected with Pseudomonas syringae. (2009) - Shah-Rossi, Devika; Heusser, Peter; Baumgartner, Stephan
Abstract : Homeopathic basic research is still in the screening phase to identify promising model systems that are adapted to the needs and peculiarities of homeopathic medicine and pharmacy. We investigated the potential of a common plant-pathogen system, Arabidopsis thaliana infected with the virulent bacteria Pseudomonas syringae, regarding its response towards a homeopathic treatment. A. thaliana plants were treated with homeopathic preparations before and after infection. Outcome measure was the number of P. syringae bacteria in the leaves of A. thaliana, assessed in randomized and blinded experiments. After a screening of 30 homeopathic preparations, we investigated the effect of Carbo vegetabilis 30x, Magnesium phosphoricum 30x, Nosode 30x, Biplantol (a homeopathic complex remedy), and Biplantol 30x on the infection rate in five or six independent experiments in total. The screening yielded significant effects for four out of 30 tested preparations. In the repeated experimental series, only the homeopathic complex remedy Biplantol induced a significant reduction of the infection rate (p = 0.01; effect size, d = 0.38). None of the other four repeatedly tested preparations (Carbo vegetabilis 30x, Magnesium phosphoricum 30x, Nosode 30x, Biplantol 30x) yielded significant effects in the overall evaluation. This phytopathological model yielded a small to medium effect size and thus might be of interest for homeopathic basic research after further improvement. Compared to Bion (a common SAR inducer used as positive control), the magnitude of the treatment effect of Biplantol was about 50%. Thus, homeopathic formulations might have a potential for the treatment of plant diseases after further optimization. However, the ecological impact should be investigated more closely before widespread application.